(untitled) (Journal of the College of Basic Education, 2023)
This research dealt with the issue of neglected roots, in the dictionary of Al-Ain, which are those words that Al-Khalil neglected on the grounds that the Arabs neglected them, and they did not use them for one reason or another. However, the Arabic-speaking linguistic community did not use all of these roots, but used what they needed.This is what Al-Khalil bin Ahmed Al-Farahidi covered in his book, and based on it his well-known theory (the used and the neglected), which is likely that he was the first to launch the label (the neglected) and meant these words that did not have a share of the Arabs’ speech and interest.This study took it upon itself to situate the negligent in the dictionary of (Al-Ain) and detail it, and to explain what it has and what it has, and from here it shows its importance as it sheds light on a distant, close, distant phenomenon; Because it is linked to the instrument that the speaking group has spoken with since ancient times, and it is close in that no one has called for it, so it puts it on the rug of scientific research.